Dark state - Stross, Charles (Stross, Charles. Empire games., 2018)
In the near future, one America is experiencing its first technological revolution <U+2013> whilst in a parallel world, the United States is a hi-tech police state. But both timelines are poised for conflict. Miriam Burgeson<U+2019>s America is heading for civil war. However, a high profile defection might avert this crisis, if only Miriam and her agents can arrange it in time. And Rita Douglas, rival US spy, arrives during this turmoil. Rita<U+2019>s world is rocked when she realizes Miriam is her birth mother, changing her own mission irrevocably. Then her United States discovers yet another parallel earth, and the remains of an advanced society. Something destroyed that civilization, Rita<U+2019>s people are about to rouse it <U+2013> and two worlds will face the consequences.